Pelatihan Pembuatan Pupuk Organik Berbahan Dasar Limbah Lontar bagi Kelompok Tani Desa Punagaya, Kecamatan Bangkala, Kabupaten Jeneponto, Sulawesi Selatan - Hiola, St. Fatmah; Syamsiah, Syamsiah; Pagarra, Halifah; Muis, Abd.; Taiyeb, A. Mushawwir (JKM: Jurnal Kemitraan Masyarakat, 2025)
This service activity is to improve the ability of partners and be able to develop and add expertise to the community, develop community knowledge about the utilization of palmyra waste so that it has use value for the environment, be able to increase income and reduce fertilizer purchases for agriculture and to develop an attitude of cooperation with others. Utilization of Palmyra waste into liquid organic fertilizer to reduce environmental pollution. The long-term benefits of using liquid fertilizer can improve the physical, chemical and biological properties of the soil. Liquid fertilizer is easy to make and the technology is simple. Lontar (Borassus flabellifer) is one of the typical plants in Jeneponto Regency which has many benefits, one of which is that it can be used as organic fertilizer. This service was carried out on farmer groups in Punagaya village, Bangkala sub-district, Jeneponto district, South Sulawesi, totaling 17 people. The results of this training activity showed that all training participants were very enthusiastic and eager to pay attention and listen to the material about the use of palm waste as organic fertilizer and how to make it delivered by the resource team. Based on the results and discussion of the implementation of activities, it can be concluded that several things including partners in this case the farmer group is able to make organic fertilizer from palm waste, and a partner group is formed that is economically and socially independent through this activity.